Pest survey card on Agrilus planipennis. Issue 11 (16th November 2020) - ,; Schans, Jan; Schrader, Gritta; Delbianco, Alice; Graziosi, Ignazio; Vos, Sybren
Abstract : This pest survey card was prepared in the context of the EFSA mandate on plant pest surveillance (M‐2017–0137), at the request of the European Commission. Its purposeisto guide the Member States in preparing data and information for Agrilus planipennis surveys. These are required to design statistically sound and risk‐based pest surveys, in line with current international standards.The buprestid beetle A. planipennis is a highly destructive Union quarantine and priority pest of ashtrees ( Fraxinus spp.) native to Asia. The pest has ravaged ash resources in North America and is currently spreading in European Russia and eastern Ukraine.The introduction of plant material of host taxa into EU Member States from areas where the pest is present is regulated.All European Fraxinus species are suitable hosts. Larvae feed on the phloem of infested ash causing extensive dieback and tree death. The beetle requires one year to complete one generation, ortwo years in colder climates. Adults are found in spring and summer. Climatic conditions in the EU territories are suitable for the establishment of A.planipennis and host trees are widely available across the EU in forests, parks and cities.The pest spreads by active flight and human‐assisted dispersalat an average rate of 1, 500 m per year. Infested trees show distinctivesymptoms and signs, but due to their late appearance surveillance based on symptoms is not suited for detection at low insect densities. The use of traps baited with attractants targeting adult beetles is an effective method to detect the pest at early stages of the infestation and is the recommended approach for implementing surveillance within the EU. The updated pest survey card for Agrilus planipennis is published and available online in the EFSA Plant Pest Survey Cards Gallery at the following link:https://arcg.is/09S94u